NETWORK METHODS OF SIMULATION OF IT PROJECT MANAGEMENT PROCESSES IN THE CONDITIONS OF THE DIGITAL ECONOMY - KOLODINSKA, Yanina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines modern challenges and opportunities to overcome them, which arise in the management of IT projects. The author noted the need to use effective management methods to achieve successful results. IIt is noted that for the purpose of rational planning and operational management of projects in the field of information technology, along with flexible methodologies, it is advisable to use network modeling methods. The key aspects of the use of network methods and models with the use of network graphs in the planning, monitoring and implementation of IT projects are presented. Their significance in planning and modeling the sequence of actions, determining the critical path and estimating the duration of the project is argued. Attention is drawn to the effectiveness of network methods in the context of complex and risky IT projects. The algorithm for finding the critical path is described, thanks to which project operations are divided into critical and non-critical ones and the minimum project execution time is determined. Methods of project analysis and optimization using a network graph and a Gantt chart are considered. Stages of modeling and calculation of parameters were carried out for the IT project on software development. The case of creating an IT product is given with a detailed overview of the network planning method and optimization according to the criteria of minimizing the cost and time of the project. It is noted that the proposed two-criteria project optimization method using a network graph is simpler and more rational compared to other mathematical methods of multi-criteria optimization. The Gantt chart for the given IT project case (table 1) was built using modern artificial intelligence tools and the FigJam digital service. Existing software solutions that significantly simplify and speed up the implementation of models and allow automating IT project management processes have been studied. The possible advantages and limitations of the use of network methods are noted, and directions for further research in this area are indicated.
Keywords: IT project management; IT product; network methods; network graph; modeling; optimization